Leadership and Advanced Degrees: Evaluating the Association Between Dual Degrees and Leadership Roles in Academic Plastic Surgery. Issue 1 (January 2022) - Pyfer, Bryan J.; Hernandez, Jorge A.; Glener, Adam D.; Cason, Roger W.; Levinson, Howard; Phillips, Brett T.
Abstract : Supplemental digital content is available in the text. Abstract : Background: There are increasingly prevalent formal educational programs for physicians who seek to be better trained to advance their fields. Although higher education and advanced degrees are not necessarily linked to leadership, we hypothesize that leaders in plastic surgery commonly have dual degrees. We sought to evaluate the prevalence of and association between additional advanced degrees in academic plastic surgery and plastic surgery leadership. Methods: Plastic surgery faculty from 96 academic training programs and all executive committee and board of directors' members from national, regional, and local plastic surgery societies were evaluated. Surgeons' institutional online profile pages, personal web pages, societal websites, and LinkedIn profiles were all evaluated for current/past leadership roles, as well as for advanced degree. Odds ratios (ORs) were used to determine if the presence of extra degrees increased their likelihood of leadership roles. Results: A total of 1036 plastic surgeons were evaluated. Sixteen percent of academic faculty have a dual degree. Furthermore, 25.5% of plastic surgeons holding formal academic leadership roles have a dual degree (OR, 2.15; P = 0.043), as do 34.4% of those serving on the executive committee or board of directors in national plastic surgery societies (OR, 2.23; P = 0.026) and 29.2% of those serving in local/regional societal leadership roles (OR, 1.96; P = 0.043). Among all dual degrees, Masters in Business Administration has the highest association with leadership roles (OR, 3.45; P = 0.002). Conclusions: Academic plastic surgeons with dual degrees are approximately twice as likely to hold a formal academic or societal leadership role. Additional studies are needed to determine if causative relationships exist.